In Martianum Capellam III: sexo divino - Pedro Manuel Suárez Martínez (Exemplaria Classica, 2008)
Translators and commentators do not agree on the interpretation of the 30th paragraph of Martianus Capella’s work. There, Jupiter appears to be consortio Iunonis, which Apollo interprets as a favourable omen. They therefore seem neither to have understood the correct value of the word tabens, from the poem immediately preceding this scene, nor, consequently, why Jupiter is said to be elatior with regard to Juno in paragraphs 39 and 40. In our opinion, since Apollo goes to his parents so that they can approve the marriage of Mercury and Philology, everything takes on a new sense if we interpret that he finds them in the midst of the sexual act.